A FIGURE AT THE CROSSROADS OF LEGEND AND REALITY: KORKYT ATA (Modern American Journal of Linguistics, Education, and Pedagogy, 2026)
Korkyt Ata is one of the most remarkable figures in the spiritual and cultural heritage of the Kazakh people, where legend and historical reality are closely intertwined. This article examines the legendary narratives surrounding Korkyt Ata’s birth, his lifelong search for immortality, his philosophical worldview, the invention of the qyl-qobyz (bowed string instrument), and the circumstances of his death. Drawing upon both folklore and historical sources, the study highlights his invaluable contribution to Kazakh culture and philosophy. It demonstrates that through his music and wisdom, Korkyt Ata expressed the philosophical concept of eternal life and left an enduring spiritual legacy for future generations.